2014
DOI: 10.1080/14789949.2014.911945
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and extra-familial child sexual abusers and recidivism in Sweden: a 10- to 15-year follow-up study

Abstract: Rates of recidivism and types of recidivist crime have varied greatly in follow-up studies of child sexual abusers. In this long-term study of a population-based cohort (n = 193) and a nationwide clinic-referred study group (n = 166) of child sexual abusers, rates of recidivism and associations between index descriptors and outcomes were compared between intra-familial offenders and extra-familial offenders. Overall, 9.8% relapsed into sexual offence, 12.4% relapsed into violence and 2.6% relapsed into both ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…This finding suggests that this group of more antisocial child molesters are relatively rare among denying sexual offenders. These findings also fit with other studies which have found recidivistic child molesters are likely to display criminal versatility, engaging in not only sexual offences but also non-sexual violence (Looman & Abracen, 2010;Nilsson et al, 2014;Nunes et al, 2007). In line with Hanson and Morton-Bourgon's (2005) observation, sexual offenders most likely to recidivate appear to be a group of persistent sexual offenders displaying an antisocial orientation, substance issues and likely impulsive with self-regulation issues.…”
Section: Discussionsupporting
confidence: 89%
“…This finding suggests that this group of more antisocial child molesters are relatively rare among denying sexual offenders. These findings also fit with other studies which have found recidivistic child molesters are likely to display criminal versatility, engaging in not only sexual offences but also non-sexual violence (Looman & Abracen, 2010;Nilsson et al, 2014;Nunes et al, 2007). In line with Hanson and Morton-Bourgon's (2005) observation, sexual offenders most likely to recidivate appear to be a group of persistent sexual offenders displaying an antisocial orientation, substance issues and likely impulsive with self-regulation issues.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, data from diverse samples are warranted. In a Swedish study of CSA offenders with a 10-to 15-year follow-up (Nilsson et al, 2014), a 10% relapse rate into sexual offences in a population-based cohort was found (n = 193). For a clinic-referred group (n =166), the relapse rate was 14%.…”
Section: Introductionmentioning
confidence: 99%
“…The reported rates for CSA reoffences vary between countries. The variance may reflect not only methodological differences, such as different data sources and definitions of recidivism, but also the earlier mentioned differences in legislation, culture and social circumstances (Nilsson et al, 2014). Thus, data from diverse samples are warranted.…”
Section: Introductionmentioning
confidence: 99%